Menstruation and injury occurrence; a four season observational study in elite female football players - Ferrer, E.; Keay, N.; Balagué-Dobón, L.; Cáceres, A.; Jarrin, P.; Rodas, G.; González, J. R. (Frontiers in Sports and Active Living, 2025)
Background: The menstrual cycle has been hypothesized to influence injury risk in female athletes due to hormonal fluctuations affecting musculoskeletal, metabolic, and neuromuscular systems. However, methodological inconsistencies and variability in phase classification have resulted in conflicting evidence. The lack of biological samples forces researchers to estimate and speculate about the relationship between the menstrual cycle and injury risk. It is well established that each phase of the cycle is characterized by specific hormonal profiles with distinct physiological functions. Without direct measurement of these hormone levels, it is difficult to generate accurate and reliable data. The only phase in which hormonal status can be confidently inferred is menstruation, as this phase is defined by low concentrations of ovarian hormones. Understanding this relationship in elite female football players is crucial for optimizing training load, health management, recovery strategies, and injury prevention.